Uganda : Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This paper discusses Uganda's Poverty Eradication Action Plan (PEAP) 2004/05-2007/08. The PEAP provides an overarching framework to guide public action to eradicate poverty. It has been prepared through a consultative process involving central and local government, parliament, donors, and civil society. The PEAP aims at contributing toward transforming Uganda into a middle-income country. The government's strategy in the short term is aimed at strengthening both agriculture and manufacturing. For agriculture, critical interventions include infrastructure, information and support to farmers' marketing. For manufacturing, the government will strengthen infrastructure, improve governance, and boost the education of the workforce.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet